2020
DOI: 10.13189/ujer.2020.080405
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Students' Psychology: The Relationship among Students' Attitudes, Persistence, Creativity, and Tolerance toward Natural Science Subjects

Abstract: This study aims to describe the relationship between students' attitudes among persistence, creativity, and tolerance in science subjects in Muaro Jambi Middle School, Jambi City Middle School, and Batanghari Regency Middle School. The research design used was quantitative associated with a correlation design. The data collection technique used is total sampling. The research subjects were 767 students. The research instruments used were closed questionnaires consisting of 54 statements of attitude questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…When they don't understand science lessons, students' reactions are lethargic, noisy, ignore classes, and do unnecessary activities. Based on the research, the problems presented also show the fairly same problem (Budiarti et al, 2016;Darmaji et al, 2020;Toma et al, 2019).Based on theoretical evidence, students who have a positive attitude will be responsible and contribute during learning activities (Astalini, Kurniawan, Darmaji, et al, 2019;Şener et al, 2015;Wan Yunus & Mat Ali, 2018). It is also known that public and private junior high school students have never measured their attitude towards science by their subject teachers.…”
Section: Introductionmentioning
confidence: 92%
“…When they don't understand science lessons, students' reactions are lethargic, noisy, ignore classes, and do unnecessary activities. Based on the research, the problems presented also show the fairly same problem (Budiarti et al, 2016;Darmaji et al, 2020;Toma et al, 2019).Based on theoretical evidence, students who have a positive attitude will be responsible and contribute during learning activities (Astalini, Kurniawan, Darmaji, et al, 2019;Şener et al, 2015;Wan Yunus & Mat Ali, 2018). It is also known that public and private junior high school students have never measured their attitude towards science by their subject teachers.…”
Section: Introductionmentioning
confidence: 92%
“…The results of the interview revealed that students were very enthusiastic about studying religion at school. They are independent in learning [36], [37]. This independence in learning indicates that students have high motivation to understand the science of religion [38], [39].…”
Section: Motivation To Study Islamic Religious In Madrasah Ibtidaiyahmentioning
confidence: 99%
“…Universities are educational institutions that offer various academic programs, including bachelor's, master's, and doctoral degrees in various fields of study [1]- [3]. In college, students can choose study programs that suit their interests and career goals [4]- [6]. This becomes an investment for a person in developing himself to be more professional.…”
Section: Introductionmentioning
confidence: 99%